Columnea longipedicellata, a new species of Gesneriaceae from Colombia - Amaya–Márquez, Marisol; Clavijo, Laura; Marín–Gómez, Oscar Humberto (Phytotaxa, 2015)
Columnea longipedicellata, a new species from Antioquia and Chocó Departments in Colombia (Cordillera Occidental) is described and illustrated. The new species is distinguished by the presence of elongate pedicels and leaves uniformly green abaxially.